MEMAKNAI INKULTURASI DALAM PENDIDIKAN SENI DAN KONSERVASI - Dody Candra Harwanto (Tonika: Jurnal Penelitian dan Pengkajian Seni, 2018)
The gradual flow of globalization influences the existence of traditional arts and cultural identities of an area that is starting to fade. In overcoming these conditions, one of the efforts that can be done is through art education and cultural conservation into new forms such as inculturation. The phenomenon of inculturation provides space for the process of art education through the development of artistic expertise, creation, and appreciation using traditional arts. In addition, efforts to conserve culture through the use of traditional arts in every procession of worship, can be a force that animates and renews the culture intensively. The pursuit of democratic cultural integration, the wealth of traditional arts in an area with all its uniqueness, beauty and cultural values can be proud of, maintained, developed and preserved, so that it can become the identity of an area and even a nation.